2010
DOI: 10.1377/hlthaff.2010.0155
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Health Information Technology On Quality In U.S. Hospitals

Abstract: Health information technology (IT), such as computerized physician order entry and electronic health records, has potential to improve the quality of health care. But the returns from widespread adoption of such technologies remain uncertain. We measured changes in the quality of care following adoption of electronic health records among a national sample of U.S. hospitals from 2004 to 2007. The use of computerized physician order entry and electronic health records resulted in significant improvements in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
145
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 14 publications
7
145
1
1
Order By: Relevance
“…Our differential findings across the three communities mirror the conflicting evidence about the impact of EHRs on healthcare utilization and associated costs (Amarasingham, Plantinga, Diener-West, Gaskin, & Powe, 2009;DesRoches et al, 2010;Himmelstein, Wright, & Woolhandler, 2010;McCullough, Casey, Moscovice, & Prasad, 2010;McCormick et al, 2012). The literature also suggests potential mechanisms that may explain the differential findings across communities.…”
Section: Discussionsupporting
confidence: 60%
“…Our differential findings across the three communities mirror the conflicting evidence about the impact of EHRs on healthcare utilization and associated costs (Amarasingham, Plantinga, Diener-West, Gaskin, & Powe, 2009;DesRoches et al, 2010;Himmelstein, Wright, & Woolhandler, 2010;McCullough, Casey, Moscovice, & Prasad, 2010;McCormick et al, 2012). The literature also suggests potential mechanisms that may explain the differential findings across communities.…”
Section: Discussionsupporting
confidence: 60%
“…The use of PACS seems to enhance both the revenue and the efficiency of hospital processes (see also Barrette et al 2011 As compared with the findings for the innovation variables, the use of CPOE and ERP seems to be of no relevance for all three performance variables (though it is for innovation), partly contrary, partly in accordance to existing USA empirical literature (McCullough et al 2010;. Finally, four applications that were tested as right-hand variables in all five estimated equations showed no significant effects at all: Radiology Information Systems (RIS),…”
mentioning
confidence: 57%
“…5 The group of the USA studies, on which we focus here, examined the impact of ICT use in hospitals on the quality of health care (Agha 2012;McCullough et al 2010), certain patient outcomes , hospital productivity (Lee et al 2012), hospital cost efficiency (PwCW2007), hospital operating costs (Borzekowski 2009) and the efficiency of the utilization of clinicians (Atkinson et al 2006). Agha (2012) in a study based on 3900 USA hospitals for the period 1998-2005 found only little impact of ICT on the quality of patient care (as measured by patient mortality, medical complication rates, adverse drug events and (patient) re-admission rates).…”
Section: Ict and Hospital Performancementioning
confidence: 99%
See 1 more Smart Citation
“…After reading the articles, we found papers with similar purposes, which were carried out by: Hospital Infantil Sabará [7], Stroetmann et al [8], Moncho [9], Schneider [10]), McCullough et al [11] and Blaya et al [12], which were then adopted as references for this article. During the conduction of the first project at Hospital Infantil Sabará, in 2012, we found a 60% decrease in paper printing.…”
Section: Resultsmentioning
confidence: 99%